Inovasi Teknologi Daur Ulang Plastik untuk Meningkatkan Efisiensi dan Profitabilitas Usaha Mikro - Hamdiah, Cut; Marlina, Marlina; Zainuddin, Zainuddin; Rahmi, Rahmi; Nabila, Sausan (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
This study explores the role of plastic recycling technology innovation in enhancing cost efficiency and profitability among micro-enterprises, while contributing to sustainable development goals. Using a qualitative literature review approach, the research synthesizes findings from international and national sources, including OECD, UNEP, UNIDO, the Indonesian Ministry of Industry, and various academic journals. The analysis identifies three main technological approaches—mechanical, chemical, and digital (smart recycling)—each offering different levels of efficiency, investment requirements, and relevance to micro-enterprises. The results indicate that mechanical recycling remains the most feasible option due to its low cost and ease of implementation, while chemical and digital recycling hold potential for long-term transformation when supported by policy and financial incentives. The study also highlights the social and environmental benefits of adopting recycling innovations, including waste reduction, job creation, and the development of green markets. Overall, technological innovation in plastic recycling serves as a strategic instrument for achieving economic efficiency, business profitability, and sustainability within Indonesia’s circular economy framework.